Pengaruh Waktu Penyimpanan Terhadap pH Sediaan Obat Kumur Ekstrak Bunga Delima Merah (Punica granatum L.) - Aulia, Annisa, drg.Mahmud Kholifa, MDSc (2017)
The high prevalence of caries indicates a lack of public awareness of Indonesia to maintain oral health. Carbohydrate-rich foods increase metabolism and acid production by oral bacteria to decrease salivary pH. The salivary buffer system takes 30-60 minutes to return salivary pH to normal saliva pH. Optimal pH of mouthwash can restore to the normal salivary pH, so it is needed to have a mouthwash from natural ingredients to maintain normal saliva pH faster. One of the herbal ingredients that can be used as an alternative to mouthwash is red pomegranate flowers (Punica granatum L.). In the storage, a change in moutwash pH can indicate the solution is less stable during storage. The purpose of this research was to know the effect of storage time on red pomegranate flower (Punica granatum L.) extract mouthwash preparations pH. The method of this research used was post test only control group design by measuring the pH of red pomegranate flower (Punica granatum L.) extract mouthwash on not stored, stored in 7 days, stored in 14 days, stored 21 days and stored in 28 days measured using pH meter. The object of research is the pH of red pomegranate flower (Punica granatum L.) extract mouthwash 0.2% which was divided into 5 treatment groups with a total of 25 samples. The result of Anova test showed p = 0,000 (p <0.05) which means that there is a significant difference of storage time to pH of the whole treatment group. The result of the post hoc LSD test showed p> 0.05 value in the treatment group which was not stored, stored for 7 days, stored for 14 days and stored for 21 days, while p <0.05 happened to be in the treatment group of 28 days storage.The conclusion of the research was pH of the red pomegranate flower (Punica granatum L.) extract mouthwash preparation changed insignificantly until the storage time was 21 days. Keywords: pH, red pomegranate extract gargle, storage time